2017
DOI: 10.21475/ajcs.17.11.10.pne542
|View full text |Cite
|
Sign up to set email alerts
|

Effects of plant growth regulators on eggplant seed germination and seedling growth

Abstract: This study aimed at evaluating the germination and the growth of eggplant (cultivar 'Embu') seedlings submitted to imbibition in GA 3 and GA 4+7 +Benzyladenine (BA). The experiment was carried out under laboratory and greenhouse conditions, adopting a completely randomized design, in a 2 x 6 factorial arrangement, i.e. two plant growth regulators (GA 3 and GA 4+7 +BA) and six imbibition conditions (no imbibition, 0, 250, 500, 750, and 1000 mg L -1 a.i.). Germination percentage, mean germination time, germinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Neto et. al also mentioned that Dickson's quality index is a good indicator for characterization of quality of eggplant seedlings [62]. Two cultivars of watermelon seedlings grown with 12 and 16 h displayed the greatest Dickson's quality index, without a significant difference between them.…”
Section: Discussionmentioning
confidence: 98%
“…Neto et. al also mentioned that Dickson's quality index is a good indicator for characterization of quality of eggplant seedlings [62]. Two cultivars of watermelon seedlings grown with 12 and 16 h displayed the greatest Dickson's quality index, without a significant difference between them.…”
Section: Discussionmentioning
confidence: 98%
“…To date, there are reports describing the benefits and drawbacks of this technology applied to eggplant ( Demir et al, 1994 ; Gomes et al, 2012 ; Gonzales, 2015 ; Neto et al, 2017 ; Ali et al, 2019 ) and its CWRs, S. torvum Swartz 1788 (turkey berry) ( Ranil et al, 2015 ; Cutti and Kulckzynski, 2016 ; Ozden and Demit, 2016 ; Sarathkumar et al, 2017 ), S. macrocarpon , S. aethiopicum , and S. incanum ( Gisbert et al, 2011 ). However, much more studies are still necessary to cover the huge biodiversity of this horticultural crop and its wild relatives.…”
Section: Introductionmentioning
confidence: 99%
“…The eggplant is an important vegetable crop, and multiple studies have been conducted to improve its low germination rate and optimize its production. Eggplant seed dormancy has been alleviated by gibberellins and potassium nitrate [16,17,18], the application of garlic extracts [19], and with organic fertilizers [20]. Here, we demonstrated that hydrogen peroxide significantly improves the eggplant seed germination rate, presenting a cheap and ecological alternative to the previously described approaches.…”
Section: Discussionmentioning
confidence: 68%